2018
DOI: 10.1002/jtr.2175
|View full text |Cite
|
Sign up to set email alerts
|

Cruise experience and its contribution to subjective well‐being: A case of Chinese tourists

Abstract: Growing evidence suggests that travel may serve as an effective intervention of subjective wellbeing (SWB). This study develops and empirically tests a psychological model that describes the links of travel experience and SWB. This study also compared the short-and long-term effects of the tourist experience on SWB. Our results identified 3 dimensions of cruise experience, namely, emotional experience, relational experience, and thinking experience. In the short term, happiness from cruise travel is created ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 72 publications
(113 reference statements)
0
16
0
Order By: Relevance
“…This two-dimensional solution is widely embraced in tourism-related research (e.g. Chi et al, 2017;Lyu et al, 2018).…”
Section: Swb: With An Emphasis On Intern Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This two-dimensional solution is widely embraced in tourism-related research (e.g. Chi et al, 2017;Lyu et al, 2018).…”
Section: Swb: With An Emphasis On Intern Studentsmentioning
confidence: 99%
“…The latter is used to measure the emotional responses and ongoing evaluation of conditions of life. This two-dimensional solution is widely embraced in tourism-related research (Chi et al, 2017;Lyu et al, 2018).…”
Section: Cultural Values and Employment Among Gen Zmentioning
confidence: 99%
“…A recent study showed that 55.8% of China' population use the Internet (CNNIC, 2018). QQ Survey was selected for its active and large online survey community in China (Lyu et al, 2017(Lyu et al, , 2018, in which nearly 5.1 million panelists had participated by 2019 (www.1diao cha.com). Compared with traditional online sampling, QQ Survey provides several important features, such as (1) control of recruitment and participant selection; (2) complete anonymity of the sample; (3) motivation to visit recruitment location; and (4) incentive disbursement through built-in payment systems.…”
Section: Survey Administrationmentioning
confidence: 99%
“…The research framework of this study presents the brand equity drivers; brand experience and brand personality as antecedents to brand engagement through the mediating role of brand affect. For instance, prior research studies have reported that brand personality and brand experience are significantly connected to brand engagement behavior through the mediating role of brand affect (Lee, Back, & Kim, 2009;Lyu, Mao, & Hu, 2018). Similarly, brand affect also significantly leads to brand engagement behavior (Samala & Singh, 2019;Verleye, Gemmel, & Rangarajan, 2014).…”
Section: Research Framework and Hypotheses Developmentmentioning
confidence: 99%
“…This study views brand experience as "subjective, internal response of customers prompted by the brand-related stimuli such as brand's identity, packaging, design, environment and communications (Brakus, Schmitt, & Zarantonello, 2009)". In the quest that if brand experience evokes positive and negative emotional response (affect), Lyu et al (2018) conducted a research study to examine this relationship. Collecting the data from Chinese tourists, the authors reported that cognitive experience is critical in evoking brand affect in customers.…”
Section: Relationship Between Brand Experience and Brand Affectmentioning
confidence: 99%